Case report: Evolution of pulmonary manifestations and virological markers in critical COVID-19 infection in Bruton’s agammaglobulinemia - Rise, Nina; Touborg, Toke; Lundsted, Ditte Helene; Dalager-Pedersen, Michael; Mogensen, Trine H. (Frontiers in Immunology, 2022)
Despite several reports and small case series on the disease course of SARS-CoV-2 infection in patients with inborn errors of immunity (IEI), including X-linked agammaglobulinemia (XLA), this topic remains incompletely described. Here we present the case of a 38-year-old unvaccinated man with XLA, who acquired SARS-CoV-2 infection and experienced a protracted disease course with 47 days of SARS-CoV-2 positivity, critical COVID-19 with respiratory insufficiency necessitating intensive care and ventilatory support, and prompting repeated intensified treatments with remdesivir, dexamethasone, and monoclonal antibodies to eventually control infection. We describe the disease course and treatment and review the current literature on COVID-19 susceptibility and evidence for vaccine efficacy in patients with XLA.